Assessing Social Inclusion of Women in Agricultural Cooperatives of Baglung Municipality, Nepal - Bhattarai, Nabraj; Sharma, Pradeep (Research Nepal Journal of Development Studies, 2024)
Cooperatives are defined as autonomous associations where members unite voluntarily to meet common economic and social needs through a jointly-owned, democratically-controlled enterprise. In this context, this study assesses multifaceted nature of women's social inclusion across three cooperatives in Baglung Municipality, Nepal. Using survey research design, data are collected from 100 women members involving in thee Cooperatives-Balewa Community Multipurpose (n=35), Nilgiri Saving & Credit (n=29), and Small Farmers Agriculture (n=36%). The findings reveal a membership profile of predominantly young and middle-aged married women (74%, mean age 32), who are primarily self-employed in agriculture (67%). However, their significant economic participation does not automatically translate to meaningful social inclusion. The study identifies a critical paradox. While intangible factors like having one's opinion valued (r = 0.548) and regular meeting participation (r = 0.485) are the strongest predictors of a woman's sense of inclusion, formal financial decision-making authority shows a surprising negative correlation (r = -0.417). This suggests that women who attain powerful positions may face social backlash or isolation. Furthermore, a severe "leadership gap" exists, with 62 percent of women remaining general members and only 4 percent in manager roles, indicating that democratic principles are not fully realized. The research concludes that conventional socio-economic indicators are insufficient to assess inclusion. Genuine empowerment requires a strategic shift in focus beyond numerical representation. The study recommends fostering an inclusive institutional culture through participatory meeting structures, targeted support for women leaders, and structural reforms like equitable advancement pathways. These measures are essential for transforming cooperatives from mere financial entities into true vehicles for gender equality and social justice in Nepal.